Conscientiousness as a protective factor in academic success in international university students - Teperman, Sarah; Siva, Chris; Mujumdar, Swati (Journal of International Students, 2026)
This study examines the role of conscientiousness as a protective factor in the academic success of international undergraduate students, who often face distinct academic and cultural adjustment challenges. Using a cross-sectional design, data were collected from a sample of international students enrolled in Australian universities. Participants completed an online questionnaire assessing conscientiousness and reported their weighted average mark (WAM) as an indicator of academic performance. The findings revealed a statistically significant positive relationship between conscientiousness and academic achievement, suggesting that higher levels of conscientiousness are associated with better academic outcomes among international students. These results highlight the importance of personality traits as consistent predictors of academic success across cultural contexts and suggest that universities and educators should foster learning environments and interventions that promote conscientious behaviors to enhance both academic performance and student well-being.